Recent Research on Catholic Parishes: A Research Note - Davidson, James D. (Review of religious research, 2006)
The landmark Notre Dame Study of Parish Life study was conducted in the 1980s. Since then, several other studies have provided additional information about Catholic parishes. We use these studies to create an overall profile of Catholic parishes. We also summarize the results of four studies indicating the similarities and differences between Protestant congregations and Catholic parishes. Finally, we examine the strengths and limitations of both the studies of Catholic parishes and studies that include both Catholics and Protestants. We conclude with some suggestions for future research.